2018
DOI: 10.2147/copd.s161555
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of COPD in China: a systematic review

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the main contributors to the global burden of disease. The aim of this systematic review was to quantify the disease burden of COPD in China and to determine the risk factors of the disease. The number of studies included in the review was 47 with an average quality assessment score of 7.70 out of 10. Reported COPD prevalence varied between 1.20% and 8.87% in different provinces/cities across China. The prevalence rate of COPD was higher among men (7.76%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
178
4
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(194 citation statements)
references
References 23 publications
4
178
4
8
Order By: Relevance
“…Moreover, the prevalence of COPD among the studied population was higher in men than in women, and increased with age. This finding aligns with many previous studies conducted in both high-income and low and middle-income countries [3,4,6,11,12]. The much higher prevalence of COPD in the present study may possibly result from the higher prevalence of current smoking (62.1% among males) in the participant population, as smoking plays a critical role in lung disease development [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the prevalence of COPD among the studied population was higher in men than in women, and increased with age. This finding aligns with many previous studies conducted in both high-income and low and middle-income countries [3,4,6,11,12]. The much higher prevalence of COPD in the present study may possibly result from the higher prevalence of current smoking (62.1% among males) in the participant population, as smoking plays a critical role in lung disease development [22].…”
Section: Discussionsupporting
confidence: 92%
“…In China, COPD ranks among the top three leading causes of death [4]. COPD prevalence has also increased, with the prevalence of COPD among people aged 40 years and over increasing from 2.7% in 1990 to 13.6% in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al and Wang et al [1,12] have shown a rate of chronic obstructive pulmonary disease (COPD) of about 2% and 2,9%, respectively. Subsequently Chen et al [10] have reported a rate of about 1% of respiratory system diseases, different from an estimated COPD prevalence between 1.2-8.9% in different regions of China [16]. Moreover, interstitial lung diseases, history of smoking, bronchiectasis or asthma were underreported [1,[4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease(COPD) is a preventable and treatable disease with characteristics of persistent respiratory symptoms and air ow limitation [1]. Because of the ageing population, tobacco exposure and heavy air pollution, the burden of COPD keep growing in China, with high prevalence in Chinese adults [2,3]. According to the Global Burden of Disease Study 2010, COPD were on the top three leading causes of death in China in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%